MODEL PEMBELAJARAN ARITMETIKA MENGGUNAKAN METODE BACKUS NAUR FORM (BNF) BERBASIS ANDROID DI SDN RAMPAL CELAKET 2 MALANG - Prayoga Wahyu Setiawan; Sujito; Liduina Asih Primandari (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2024)
The increasing technological development of Android-based devices can be used as an opportunity to solve the problems in the study of arithmetic. The way to solve the problem is create an android-based application learning arithmetic. To make the application, required a method that can be used to detect the pattern of arithmetic that can be processed into applications to be petrified understand the arithmetic processing step. Matter of arithmetic is a sequence of characters that are similar to script programming language. Both have a pattern of certain rules that must be followed to avoid mistakes in the stage of processing results. The method can be used to search for patterns in a particular rule is Backus Naur Form. BNF is a metalanguage syntactic commonly used as a notation for the present generation of language. Most compilers such as Turbo, and MinGW using the BNF for parsing script programming.